2015
DOI: 10.1177/1362361314564473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the appropriateness of a new computer-administered measure of adaptive function for children and youth with autism spectrum disorders

Abstract: The Pediatric Evaluation of Disability Inventory-Computer Adaptive Test is an alternative method for describing the adaptive function of children and youth with disabilities using a computer-administered assessment. This study evaluated the performance of the Pediatric Evaluation of Disability Inventory-Computer Adaptive Test with a national sample of children and youth with autism spectrum disorders aged 3–21 years. Parents (n = 365) completed an online survey that included demographics, the Social Communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Recent psychometric testing [7] of the PEDI-CAT (ASD), a slightly modified version of the original PEDI-CAT, with youth with autism showed acceptable values from CFA, which confirmed the validity of the three-domain structure for this group. Further, almost all items on the PEDI-CAT (ASD) had acceptable fit, indicating that items continue to fit along a unidimensional continuum for this population.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Recent psychometric testing [7] of the PEDI-CAT (ASD), a slightly modified version of the original PEDI-CAT, with youth with autism showed acceptable values from CFA, which confirmed the validity of the three-domain structure for this group. Further, almost all items on the PEDI-CAT (ASD) had acceptable fit, indicating that items continue to fit along a unidimensional continuum for this population.…”
Section: Introductionmentioning
confidence: 76%
“…Our previous analysis indicated that the PEDI-CAT domains maintain strong psychometric properties when used with children and youth with autism [7]. However, as noted earlier, about half the items in the Social/Cognitive domain were found to have significant DIF using a logistic regression approach [7].…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This approach has been applied successfully elsewhere. 17 However, if the cognitive interviews suggest that some other factor – such as lack of understanding or a different interpretation of meaning, difficulty in making the comparison implied in the item, or impact of other clinical factors such as vision or upper extremity limitations – is influencing responses, this would indicate that the responses of children and adolescents with CP are not reflecting the same construct, which is a validity issue.…”
Section: Discussionmentioning
confidence: 99%